Analysis of maternal–fetal heart rate coupling directions with partial directed coherence. (September 2016) - Khandoker, Ahsan H.; Marzbanrad, Faezeh; Voss, Andreas; Schulz, Steffen; Kimura, Yoshitaka; Endo, Miyuki; Palaniswami, Marimuthu
Abstract: Maternal psycho-physiological activities affect the fetal heart rate and heart rate variability. However, directions and patterns of maternal and fetal heartbeat coupling are still poorly understood. The aim of this study was to quantify the direction of short-term maternal–fetal cardiac coupling in early, mid and late gestation fetuses by using partial directed coherence (PDC) analysis approach. The analysis was based on fetal electrocardiograms (fECGs) of 66 healthy fetuses; 22 from early gestation 16–25 weeks, 22 from mid gestation 26–30 weeks and 22 from late gestation 32–41 weeks. Results of analyzing PDC demonstrated a causal influence of fetal on maternal heart rate in the early gestation, while it significantly decreased from early to mid gestation along with a significant increase of maternal to fetal coupling strength. The causal influence of maternal on fetal heart rate was the strongest in the mid gestation and remained dominant in the late gestation. In conclusion, the application of PDC revealed detailed information about short-term maternal–fetal cardiac couplings and regulatory mechanisms (patterns) of developing autonomic nervous system function.